2019
DOI: 10.1177/1945892418823388
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics-Based Approaches Predict That MIR-17-5P Functions in the Pathogenesis of Seasonal Allergic Rhinitis Through Regulating ABCA1 and CD69

Abstract: Objective As the most prevalent type of rhinitis, allergic rhinitis is consisted of seasonal allergic rhinitis (SAR) and perennial allergic rhinitis. This study is carried out for revealing the mechanisms of SAR. Methods Microarray data set GSE43523 (including 7 SAR nasal epithelial cells and 5 nonallergic control nasal epithelial cells) was extracted from Gene Expression Omnibus database. Based on limma package, differential expression analysis for the 2 groups was performed to obtain differentially expressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…miR-17-5p expression was elevated in OVAinduced AR model mice, and its expression was reduced by circDdx17 overexpression. Liu et al, using bioinformaticsbased approaches, showed that miR-17-5p exerts its function via ABCA1 and CD69 in the pathogenesis of seasonal AR [32].…”
Section: Discussionmentioning
confidence: 99%
“…miR-17-5p expression was elevated in OVAinduced AR model mice, and its expression was reduced by circDdx17 overexpression. Liu et al, using bioinformaticsbased approaches, showed that miR-17-5p exerts its function via ABCA1 and CD69 in the pathogenesis of seasonal AR [32].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, two studies focused on DEGs from the nasal epithelial cells of AR patients [ 9 , 30 ]. Another study focused on DEGs and the transcription factor (TF)-miRNA network only in nasal epithelial cells and showed that miR-17-5P might act in SAR by targeting ATP binding cassette subfamily A member 1 (ABCA1) and CD69 [ 31 ]. Additionally, a study on DEGs in adult and pediatric nasal epithelial cells a found that AP-1 was associated with AR by regulating cystatin SN (CST1) and Charcot–Leyden crystal galectin (CLC) [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The development of novel therapeutic options often relies on a deeper understanding of signaling pathways and gene expression patterns in inflammatory processes such as allergic rhinitis, and 2 articles in this issue attempt to improve our understanding of allergic rhinitis. Liu et al 2 explored the underlying mechanisms of allergic rhinitis with microarray data from the Gene Expression Omnibus, identified 274 genes differentially expressed in allergic rhinitis, and utilized multiple bioinformatics approaches to identify future candidate genes for experimental research and as potential therapeutic targets. Pirayesh and colleagues 3 evaluated the expression of Fas receptor, a member of the tumor necrosis factor superfamily with a prominent role in regulation of the immune system, in the inferior turbinate mucosa.…”
mentioning
confidence: 99%